EFFECT OF LONG-TERM STARVATION ON BRANCHIAL TISSUE GLYCOLYSIS OF FRESHWATER FISH, TILAPIA MOSSAMBICA (PETERS) - Haranath, V Bhaskara; Bhaskar, M; Rao, M V Chalapathy; Rani, P Shobha; Reddanna, P; Govindappa, S (Indian Journal of Fisheries, 2011)
The activity levels of phosphorylases, aldolase and LDH were significantlysuppressed with depleted lactic acid content, indicating decreased glycolysis of thetissue of fish subjected to long term starvation. The suppression of glycolysis wascorrelated towards the regulation of the tissue glycogenolysis and decreased oxygenuptake of the fish.